Modeling e-loyalty: a moderated-mediation model. Issue 15 (10th December 2018) - Lin, Chieh-Peng; Chiu, Chou-Kang; Liu, Chu-Mei; Chen, Kuang-Jung; Hsiao, Chieh-Yu
ABSTRACT: This work proposes a research model that elaborates upon the development of e-loyalty based on the signaling theory and attachment theory. In the model, e-loyalty is indirectly related to both visual appeal and an e-tailer's service reputation through the full mediation of trust and affection. At the same time, the relationships between trust and e-loyalty and between affection and e-loyalty are hypothetically moderated by an e-tailer's service reputation. The proposed hypotheses of this research were empirically tested using data from working professionals in high-tech firms in terms of online retailing. This study surveyed the same research participants at two different time points, one month apart, to verify the theoretical inferences. The empirical findings herein complement the previous literature by presenting how visual appeal and an e-tailer's service reputation simultaneously influence e-loyalty through various mediating and moderating mechanisms.